2020
DOI: 10.3390/molecules25112692
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Polymer-Based Nanoparticle siRNA Delivery Systems for Cancer Therapy

Abstract: RNA interference (RNAi) uses small interfering RNAs (siRNAs) to mediate gene-silencing in cells and represents an emerging strategy for cancer therapy. Successful RNAi-mediated gene silencing requires overcoming multiple physiological barriers to achieve efficient delivery of siRNAs into cells in vivo, including into tumor and/or host cells in the tumor micro-environment (TME). Consequently, lipid and polymer-based nanoparticle siRNA delivery systems have been developed to surmount these physiological barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 89 publications
1
82
0
1
Order By: Relevance
“…Tseng et al, reported that CIS-incorporated gelatin nanocomplexes can be used for cancer chemotherapy (46). Lipid and polymer-based nanoparticles siRNA delivery systems are also developed by Mainini et al, to cancer therapy (47). Polymeric nanoparticles synthesized based on hostguest interaction between β-cyclodextrin and benzimidazole used for liver cancer-targeted therapy and its ability to induce cell apoptosis was found to be remarkable (48).…”
Section: Discussionmentioning
confidence: 99%
“…Tseng et al, reported that CIS-incorporated gelatin nanocomplexes can be used for cancer chemotherapy (46). Lipid and polymer-based nanoparticles siRNA delivery systems are also developed by Mainini et al, to cancer therapy (47). Polymeric nanoparticles synthesized based on hostguest interaction between β-cyclodextrin and benzimidazole used for liver cancer-targeted therapy and its ability to induce cell apoptosis was found to be remarkable (48).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are not any preclinical trials concerning circRNAs in clinical treatment for cancer, numerous studies and attempts to utilize siRNAs as therapeutics have been reported. 53 , 54 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…Many recent delivery vehicles have taken advantage of the change from extracellular to the endosomal environment. Among the many differences, the change in pH is often utilized for efficient endosomal disruption and further release of siRNA once inside the target cell [ 117 ]. Protonable cationic polymers have been shown to increase delivery efficiency due to their high buffering capacity [ 45 ].…”
Section: Endosomal Escapementioning
confidence: 99%